ANALISIS PENERAPAN STRATEGI PROMOSI BELOW THE LINE TERHADAP PENINGKATAN JUMLAH NASABAH DI PT. BANK TABUNGAN NEGARA KANTOR CABANG SYARIAH MEDAN - Luthfia Nabila Pane; Marliyah Marliyah; Laylan Syafina (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to determine the implementation of the Below The Line promotion strategy at the State Savings Bank, Medan Syariah Branch Office. The Below The Line promotion strategy is implemented to attract customers to save and transact at BTN Syariah Medan Branch Office and can increase the number of customers at the bank. This study uses a descriptive qualitative approach with primary and secondary data sources. This study uses data collection techniques with interviews and documentation studies by coming directly to BTN Syariah and interviewing existing sources. As well as using data on the increase in the number of customers in the last 5 years at BTN Syariah. The results of this study indicate an increase in the number of customers at BTN Syariah in the last 1 year. Based on the Annual Report of BTN Syariah Medan Branch Office from 2019 to 2020 there was an increase in the number of customers by 32.6% from 2019. That is from 713,747 in 2019 to 816,422 in 2020. And the implementation of the Below The Line promotion strategy has a big influence on an increase in the number of customers at BTN Syariah KC Medan. Below The Line Promotion Strategy types of Events, Sponsorships and Prizes greatly affect the increase in the number of customers at BTN Syariah Medan Branch Office. Then, the obstacles that exist in the implementation of the Below The Line Promotion Strategy have also been found solutions to overcome them so that in the future it is hoped that the Below The Line Promotion Strategy can run smoothly. Then from the results of this study, the type of Below The Line Promotion Strategy that has the most influence on increasing the number of customers at BTN Syariah Medan Branch Office is Event.